Digital Transformation in the Management of Private Islamic Higher Education Institutions: Opportunities and Challenges - Zaenal Abibin; AL-Momani, Mohammad Omar; Aliamat Omar Ali (Zabags International Journal of Education, 2025)
Digital transformation has become a strategic issue in higher education management, including in Perguruan Tinggi Islam Swasta (PTIS), which are required to enhance academic service quality, management effectiveness, and competitiveness in the global era. This study aims to describe the implementation of digital transformation in PTIS management, identify opportunities, analyze challenges, and propose optimization strategies. A qualitative approach, employing a case study strategy, was used. Data were collected through observations, in-depth interviews with university leaders, lecturers, administrative staff, and students, as well as institutional documents and policies. The findings indicate that PTIS has implemented various systems, including SIAKAD (an academic information system), a Learning Management System (LMS), digital libraries, and technology-based financial services. Nevertheless, obstacles remain, including limited infrastructure, resistance among some lecturers, low digital literacy, and financial constraints. At the same time, digitalization opens up opportunities for greater transparency in governance, improved administrative efficiency, expanded access to learning, and stronger Good University Governance. These findings underscore the importance of adaptive management strategies, systematic human resource capacity-building, and sustainable infrastructure investment to ensure effective and relevant digital transformation in PTIS.